Efficacy and safety of nilotinib 300 mg twice daily in patients with chronic myeloid leukemia in chronic phase who are intolerant to prior tyrosine kinase inhibitors: Results from the Phase IIIb ENESTswift study. (April 2018) - Hiwase, Devendra; Tan, Peter; D'Rozario, James; Taper, John; Powell, Anthony; Irving, Ian; Wright, Matthew; Branford, Susan; Yeung, David T.; Anderson, Luke; Gervasio, Othon; Levetan, Carly; et al.
Highlights: Treatment of CML-CP with a TKI may lead to intolerable adverse events. Switching to an alternative TKI is an option. 20 CML-CP patients intolerant of imatinib or dasatinib switched to nilotinib. 50% of patients achieved MR4.5 at any time point up to month 24. Nilotinib showed minimal cross intolerance. Abstract: Background: Some patients receiving a tyrosine kinase inhibitor (TKI) for the first-line treatment of chronic phase chronic myeloid leukemia (CML-CP) experience intolerable adverse events. Management strategies include dose adjustments, interrupting or discontinuing therapy, or switching to an alternative TKI. Methods: This multicenter, single-arm, Phase IIIb study included CML-CP patients intolerant of, but responsive to, first-line treatment with imatinib or dasatinib. All patients were switched to nilotinib 300 mg bid for up to 24 months. The primary endpoint was achievement of MR4.5 (BCR-ABL transcript level of ≤0.0032% on the International Scale) by 24 months. Results: Twenty patients were enrolled in the study (16 imatinib-intolerant, 4 dasatinib-intolerant); which was halted early because of low recruitment. After the switch to nilotinib 300 mg bid, MR4.5 at any time point up to month 24 was achieved in 10 of 20 patients (50%) in the full analysis set. Of the non-hematological adverse events associated with intolerance to prior imatinib or dasatinib, 74% resolved within 12 weeks of switching to nilotinib 300 mg bid. Conclusion: Nilotinib 300 mg bid shows minimal cross intolerance in patients with CML-CP who have prior toxicities to other TKIs and can lead to deep molecular responses.